Intramedullary spinal cysticercosis simulating a conus medullaris tumor: case report - Guedes-Corrêa José Fernando; Macedo Ricardo Caratta; Vaitsman Rafael Pereira; Mattos Jorge Gomes de; Agra Jovita Marques (Arquivos de Neuro-Psiquiatria)
Cysticercosis is an endemic condition in many developing countries. Although it is the most common parasitic disease of the central nervous system, cysticercal involvement of the spinal cord is rare. It may occur as intradural extramedullary, intramedullary, intramedullary associated with intradural-extramedullary or as the vertebral presentation. We report the case of a 53-year-old woman who presented with low back pain of acute onset and no other symptoms. Magnetic resonance imaging (MRI) showed an intramedullary cyst of the conus medullaris region which, at pathological examination, was diagnosed as a cysticercal cyst. She refused anticysticercal agents and steroids postoperatively. After an eight-year follow-up, the patient performs the activities of her daily living with no difficulties, and annual spinal MRIs show no residual signs of the disease. Clinical, pathofisiological, diagnostic and therapeutic aspects of spinal cord intramedullary cysticercosis are discussed.